2015
DOI: 10.1186/s12891-015-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing parecoxib and ketorolac as preemptive analgesia in patients undergoing posterior lumbar spinal fusion: a prospective randomized double-blinded placebo-controlled trial

Abstract: BackgroundPoor postoperative pain control is frequently associated with complications and delayed discharge from a hospital. Preemptive analgesia is one of the methods suggested for reducing postoperative pain. Opioids are effective for pain control, but there known addictive properties make physicians cautious about using them. Parecoxib and ketorolac are potent non-opioid NSAIDs that are attractive alternative drugs to opioids to avoid opioid-related side effects. However, there are no good head-to-head comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
(37 reference statements)
1
43
1
2
Order By: Relevance
“…Of the 14 RCTs that evaluated systemic pharmacological therapies to prevent and treat postoperative pain after lumbar spine procedures, pregabalin was tested in 7 RCTs, nonsteroidal anti‐inflammatory drugs (NSAIDs) in 2 RCTs, and other drugs (dexamethasone, minocycline, propofol, sevoflurane, paracetamol, naproxen, ketamine, and clonidine) in the remaining 5 RCTs . Of the 7 RCTs that tested pregabalin, 4 demonstrated that pregabalin alone or in association with other drugs was more effective than placebo, 1 that it was as effective as placebo, and 2 that it was more effective than morphine in preventing postoperative pain .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 14 RCTs that evaluated systemic pharmacological therapies to prevent and treat postoperative pain after lumbar spine procedures, pregabalin was tested in 7 RCTs, nonsteroidal anti‐inflammatory drugs (NSAIDs) in 2 RCTs, and other drugs (dexamethasone, minocycline, propofol, sevoflurane, paracetamol, naproxen, ketamine, and clonidine) in the remaining 5 RCTs . Of the 7 RCTs that tested pregabalin, 4 demonstrated that pregabalin alone or in association with other drugs was more effective than placebo, 1 that it was as effective as placebo, and 2 that it was more effective than morphine in preventing postoperative pain .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 RCTs that tested pregabalin, 4 demonstrated that pregabalin alone or in association with other drugs was more effective than placebo, 1 that it was as effective as placebo, and 2 that it was more effective than morphine in preventing postoperative pain . The 2 RCTs that tested NSAIDs showed that parecoxib, ketorolac, and etoricoxib were more effective than placebo in preventing postoperative pain . Dexamethasone, paracetamol, and the combination of ketamine‐clonidine led to positive results on postoperative pain prevention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations